La Hispania en época de Augusto vista por los escriores contemporáneos. Estrabón y Trogo Pompeyo - Blázquez Martínez, José María (Gerión. Revista de Historia Antigua, 2006)
A description of Hispania in time of Augustus has been narrated to us by Strabo and Trogo Pompeius. The first of them, although he did not visit the country, left a description in his third book. About Trogo Pompeius, although his work is lost, we know about thanks to Pliny, the Elder, and the Epitome made by Justin. Strabo shows more interest in the South, describing the wealth of the Turdetania, fishes, mines, agriculture. Trogo Pompeius wrote a laus of Hispania with incidence in the Second Punic War.